Soybean residue incorporation enhances soil CO₂ emissions by increasing nutrient availability and alleviating microbial phosphorus limitation - Xiongde Dong; Yutong Xiao; Mai-He Li; Shijie Han; Yating Deng; Yanyan Yu; Feirong Ren; Junqiang Zheng (Applied Soil Ecology, 2026)

Semiconducting polymer-based ratiometric fluorescent nanoprobe for highly accurate imaging of H2S in inflammatory and tumor cells - Chen Han; Xing Wang; Yating He; Rong Wang; Hong-Min Meng; Lin Zhang; Zhaohui Li (Analytica Chimica Acta, 2026)

Enantioselective migration, degradation, and metabolism of pyriproxyfen and its metabolites from tea garden to cup - Hongxia Li; Yue Hu; Yating Ning; Qing Zhong; Hezhi Sun; Xinru Wang; Mei Yang; Fengjian Luo; Li Zhou; Bingjun Han; Xinzhong Zhang (Food Chemistry, 2026)

Low-carbon and resilient innovation in traditional biomass fire-pit heating: coupling residual heat with natural ventilation to enhance nighttime thermal comfort - Wenyang Han; Chang Yi; Yating Duan; Zhixiang Zuo; Yang Yang; Mingrui Zhang; Yan Bai; Yue Xie; Yin Zhang; Kai Xie (Building and Environment, 2026)

The aging eye: navigating molecular mechanisms and innovative interventions - Yumeng Lin; Zhongyu Han; Yunfeng Zhang; Ruimin Yuan; Mingyu Huang; Yating Liu; Jun Wang; Chen Xu; Luze Liu; Ping Yu; Qingsong Yang; Liuzhi Zeng; et al. (Biogerontology, 2026)

Synergistic construction of OSA-ferulic acid composite starch: Structural evolution, gel properties, and its regulation on lamb meat flavor - Meijuan Xu; Pei Yan; Xinfeng Yue; Yating Han; Xi Han; Linping Yao; Xiaojing Ma; Yuanbo Xiao; Dequan Wei; Jian Zou (Food Research International, 2026)

Directed charge transfer in a chitosan-citric acid/NH2-UiO-66 hybrid via an amide bond bridge for photocatalytic co-production of benzaldehyde and H2O2 - Yating Lu; Huixia Zhu; Yue Han; Yu Tian; Xiaoxia Liang; Dongyu Nie; Tingming Ye; Yixu Peng; Xia Yang (Chemical Engineering Journal, 2026)

Towards sustainable municipal solid waste treatment: Life cycle environmental-economic analysis under waste sorting - Chenqi Gao; Rongxing Bian; Chengyue Yin; Xinran Du; Haoran Han; Yating Niu; Yingjie Sun; Yanan Wang (Journal of Environmental Sciences, 2026)

Chronic nanoplastics exposure drives lung cancer progression through ATF3/PCK2 axis-mediated rewiring of truncated gluconeogenesis - Qian Li; Wenwen Meng; Chengting Xie; Fei Wang; Yating Deng; Keying Chen; Yi Li; Yuqiao Li; Yixian Wen; Jing Zhu; Tingli Han; Xuemei Chen; et al. (Journal of Hazardous Materials, 2026)

Combined high voltage atmospheric cold plasma and ultraviolet-cold plasma inhibited Aspergillus flavus growth and improved physicochemical properties of protein in peanuts - Luling Zhao; Jiarong Zheng; Wenjing Yan; Jing Qian; Jianhao Zhang; Jin Wang; Xiaowei Sheng; Vijaya Raghavan; Xiaohan Yang; Yuxuan Han; Taotao Cao; Yating Chen (Food Chemistry, 2025)

Organic fertilizer significantly mitigates N2O emissions while increase contributed of comammox Nitrospira in paddy soils - Han Sun; Youfa Li; Yating Xing; Dylan Bodington; Xing Huang; Chenxiao Ding; Tida Ge; Hongjie Di; Jianming Xu; Cécile Gubry-Rangin; Yong Li (Science of The Total Environment, 2024)

Multi-level pumping water system from bioengineering wood microstructure by self-growing mycelium for boosting photothermal evaporation efficiency - Yuzhang Lei; Yating Sun; Yanda Li; Kai Han; Gonggang Liu; Shanshan Chang; Yuan Zhu; Xianjun Li; Yue Liu; Jinbo Hu (Chemical Engineering Journal, 2024)

Resilience analysis of the RCEP shipping network - Jiaguo Liu; Yating Fu; Kangkang Han; Ying Cui (Ocean & Coastal Management, 2024)

Serum arsenic augments gallstone risk in Henan rural cohort with multiple metal exposure - Qian Zhang; Yating Li; Han Hu; Meichen Tian; Tingting Cao; Hui Wu; Weidong Wu; Guofu Zhang (Science of The Total Environment, 2024)

Impacts of future climate change on rice yield based on crop model simulation—A meta-analysis - Na Li; Yating Zhao; Jinsheng Han; Qiliang Yang; Jiaping Liang; Xiaogang Liu; Yazhou Wang; Zhengzhong Huang (Science of The Total Environment, 2024)

Exploring a specialized programmed-cell death patterns to predict the prognosis and sensitivity of immunotherapy in cutaneous melanoma via machine learning - Leyang Xiao; Ruifeng He; Kaibo Hu; Gelin Song; Shengye Han; Jitao Lin; Yixuan Chen; Deju Zhang; Wuming Wang; Yating Peng; Jing Zhang; Peng Yu (Apoptosis, 2024)

The association between blue light exposure and incidence of type 2 diabetes: A prospective study of UK biobank - Cheng Wang; Yang Zhao; Qianqi Hong; Yating Lei; Shengyuan Wang; Weiqi Wang; Wei Wei; Changhao Sun; Tianshu Han (Environmental Research, 2024)

Grey matter structural alterations in anxiety disorders: a voxel-based meta-analysis - Han Liu; Zeqi Hao; Shasha Qiu; Qianqian Wang; Linlin Zhan; Lina Huang; Youbin Shao; Qing Wang; Chang Su; Yikang Cao; Jiawei Sun; Chunjie Wang; et al. (Brain Imaging and Behavior, 2023)

Facilely adjusting acidity features of zeolites by steaming treatment for enhanced methanol conversion to aromatics: A mechanism study - Zhenjun Xu; Tingjun Fu; Yating Han; Zhong Li; Guowu Zhan (Fuel, 2023)

Zirconium and neodymium isotopes record intensive felsic volcanism in South China region during the Permian-Triassic boundary crisis - Yu Jiao; Lian Zhou; Thomas J. Algeo; Lanping Feng; Jun Shen; Yating Hu; Jinhua Liu; Yan Han; Xin Hou (Chemical Geology, 2023)

Insights into autotrophic carbon fixation strategies through metagonomics in the sediments of seagrass beds - Xiangqun Chi; Zhiyi Zhao; Qiuxia Han; Huaxiao Yan; Bei Ji; Yating Chai; Shengying Li; Kun Liu (Marine Environmental Research, 2023)

Promoting photocatalytic performance of TiO2 nanomaterials by structural and electronic modulation - Han Cao; Fangyuan Liu; Yating Tai; Wei Wang; Xiaoyu Li; Pengyao Li; Hongzuo Zhao; Yongqing Xia; Shengjie Wang (Chemical Engineering Journal, 2023)

Screening of host gut-derived probiotics and effects of feeding probiotics on growth, immunity, and antioxidant enzyme activity of hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Yating Zhu; Wen Li; Mingqing Zhang; Zhongxuan Zhong; Zhiqian Zhou; Jiayi Han; Cuiping Zhang; Jinlin Yang; Yuxin Wu; Hu Shu (Fish & Shellfish Immunology, 2023)

Remediation of heavy-metal-contaminated soil with two organic acids: Washing efficiency, recovery performance, and benefit analysis - Zilin He; Lulu Long; Han Yuan; Han Pang; Yating Wang; Liang Ye; Min Xu; Chao Chen; Yan Liu; Yinlong Xiao; Changlian Xu; Jun Wu; et al. (Journal of Cleaner Production, 2023)

Decadal Changes in the Annual Growth of Two Commercial Ommastrephid Species in the Pacific Ocean - Peiwu Han; Jianhua Li; Yating Dan; Bilin Liu; Xinjun Chen; Zhou Fang (Fishes, 2022)
Neon flying squid Ommastrephes bartramii and jumbo flying squid Dosidicus gigas are two important commercial ommastrephid species in the Pacific Ocean. As short-lived marine species, squids are highly susceptible to changes in climate and marine environments. According to samples collected from the northwest and southeast Pacific Ocean in different years, we explored the growth characteristics of these two squids in terms of their mantle length (ML) distribution and the relationship between mantle length and body weight (LWR), also considering the relative condition factors (Kn), and explored the effects of the El Niño and Southern Oscillation (ENSO) on their growth. The results showed that the ML for O. bartramii and D. gigas had significant differences among different years and different sexes (p 3), and parameters a and b were influenced by year and sex. Furthermore, there were significant differences in Kn in both squids for different years and different sexes (p

Microfossil analysis of dental calculus and isotopic measurements reveal the complexity of human-plant dietary relationships in Late Bronze Age Yunnan - Tingting Wang; Dong Wei; Zhilong Jiang; Xiumin Xia; Yan Wu; Zhen Han; Yating Qu; Yaowu Hu; Benjamin T. Fuller (Archaeological and Anthropological Sciences, 2022)

Pore-scale study on the characteristic hydraulic conductivity of a dispersive lean clay affected by salinity and freeze–thaw - Yan Han; Qing Wang; Jing Liu; Weitong Xia; Jiaqi Wang; Jiejie Shen; Yating Chen (Bulletin of Engineering Geology and the Environment, 2022)

Inhalation cancer risk estimation of source-specific personal exposure for particulate matter–bound polycyclic aromatic hydrocarbons based on positive matrix factorization - Bin Han; Yan You; Yating Liu; Jia Xu; Jian Zhou; Jiefeng Zhang; Can Niu; Nan Zhang; Fei He; Xiao Ding; Zhipeng Bai (Environmental Science and Pollution Research, 2019)

A new biflavonoid and a new triterpene from the leaves of Garcinia paucinervis and their biological activities - CuiCui Jia; Tong Han; Jun Xu; ShengGe Li; YaTing Sun; DaHong Li; ZhanLin Li; HuiMing Hua (Journal of Natural Medicines, 2017)

Assessing the inhalation cancer risk of particulate matter bound polycyclic aromatic hydrocarbons (PAHs) for the elderly in a retirement community of a mega city in North China - Bin Han; Yating Liu; Yan You; Jia Xu; Jian Zhou; Jiefeng Zhang; Can Niu; Nan Zhang; Fei He; Xiao Ding; Zhipeng Bai (Environmental Science and Pollution Research, 2016)

Network analysis of eight industrial symbiosis systems - Yan Zhang; Hongmei Zheng; Han Shi; Xiangyi Yu; Gengyuan Liu; Meirong Su; Yating Li; Yingying Chai (Frontiers of Earth Science, 2016)